Functional Properties of Natural Products and Human Health - Rigano, Daniela; Bontempo, Paola (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue are collected original research articles, short communications, and reviews on new perspectives for the chemical and functional properties of natural products, including the molecular mechanisms behind the therapeutic effects of natural products used to treat human diseases. This reprint is addressed to all researchers interested in the studies about the bioavailability and biological effects of natural products isolated from plants and algae.